Quality of service class mapping and scheduling scheme for converged LTE-WiFi in the next generation networks. (2nd July 2019) - Saeed, Amer T.; Esmailpour, Amir
In this paper, a novel quality of service (QoS) class mapping and scheduling scheme for the LTE-WiFi converged network is proposed to ensure that end-to-end QoS support is provisioned seamlessly. A mapping among QoS classes of LTE and WiFi is performed first, then scheduling scheme is outlined. For scheduling scheme, traffic is separated into real-time (RT) and non-real-time (NRT) components, then a two-stage complex queuing strategy is performed. In the first stage, deficit weighted round robin queuing (DWRRQ) and class-based weighted fair queuing (CBWFQ) are used for RT and NRT applications respectively to segregate and forward traffic according to resource requirements. Whereas in the second stage, rate-control priority queuing (RCPQ) is used for all types of traffic to give each class appropriate priority level. Performance evaluation of the converged network was done based on different metrics such as jitter, end-to-end delay, throughput, and packet loss ratio. Simulation results show significant improvements for RT with slight degradation on NRT applications after using the new scheduling scheme.